Closure of a large lumbosacral myelomeningocele post operative defect with a human cadaveric split-thickness skin graft: a case report - Campos-Lopez, Diana E.; Sauceda-Elenes, Nora C.; Martinez-Jimenez, Mario A.; Cardenas-Cruz, Cristopher; Jiménez-Santana, Lizeth; Jiménez-Sierra, Mariana G.; Medellin-Cristerna, Rito J.; Arias-Mendoza, Alejandro (International Journal of Research in Medical Sciences, 2022)
Spina bifida is the most common birth defect of the central nervous system that is compatible with life, and myelomeningocele represents its most frequent form. Congenital myelomeningocele (CMM) has a worldwide incidence of 0.5 to 0.8 per 1,000 live newborns. CMM is a complex condition resulting from incomplete closure of the neural tube, mainly in the lumbosacral region. The objective of the surgical repair of the CMM is the reconstruction of all the tissue layers of the defect, avoiding possible postoperative complications. The aim of this case review is to present a re-epithelialization closure in a patient with a large CMM defect in who primary hermetic closure was not possible because there was too much tension at the edges of the defect. Therefore, human cadaveric split-thickness skin grafts were placed over the dura mater and the aponeurotic layer, covering the entire defect and an adequate healing and completely closure of the defect were observed in eight weeks. The surgical management of large meningomyelocele defects represents a major challenge and no single protocol exists for its reconstruction. The repair of an MMC defect should be performed during the first 72 hours after birth. After neurosurgical closure of the neural tube and dura, the myelomeningocele defect requires good quality skin and subcutaneous tissue with minimal wound tension for stable coverage. Human cadaveric skin grafts are considered a useful technique for temporary wound coverage because they lead to a more natural healing environment, possess ideal properties, and provide a physiological barrier that reduces microbiological contamination, in addition, it acts as a bridge to adhere to and to seal wound beds.